Migrants as agents in placemaking: A socio-spatial analysis of Basmane area in Izmir, Türkiye - Ayselin Yıldız; Aylin Gürel; Meltem Ö. Gürel (Wellbeing, Space and Society)
This article explores the place-making practices of displaced Syrian refugees living in Basmane area of Izmir's historic Konak district. By examining everyday spaces, the spatio-material and socio-relational outcomes of Syrians’ placemaking practices, the study positions refugees as active agents of placemaking. Through empirical fieldwork, it underscores the spatio-material consequences and socio-relational wellbeing outcomes of Syrians’ placemaking practices, illustrating how these are shaped and constrained by multi-scale configurations of Türkiye's refugee policies and the perceptions of the local population towards migrants.